2018
DOI: 10.3389/fpls.2018.01605
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Short- and Long-Term Variation in Resource Conditions on Soil Fungal Communities and Plant Responses to Soil Biota

Abstract: Soil biota can strongly influence plant performance with effects ranging from negative to positive. However, shifts in resource availability can influence plant responses, with soil pathogens having stronger negative effects in high-resource environments and soil mutualists, such as arbuscular mycorrhizal fungi (AMF), having stronger positive effects in low-resource environments. Yet the relative importance of long-term vs. short-term variation in resources on soil biota and plant responses is not well-known. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 89 publications
(131 reference statements)
1
5
1
Order By: Relevance
“…Soil biota also reduced C. stoebe leaf mass area (LMA), while soil biota effects on root to shoot ratios depended on soil moisture and presence of a competitor. Similar changes in LMA have been observed previously (Hahn et al, 2018) and could be caused by AM fungi, because LMA decreases when carbon availability is lowered (Poorter et al, 2009) and AM fungal colonization induces a substantial carbon-sink (Drigo et al, 2010). Soil biota significantly reduced root to shoot ratios of C. stoebe which fits with early observations of AM fungi reducing root to shoot ratios in C. stoebe (Marler, Zabinski, Wojtowicz, et al, 1999), possibly because AM fungi substitute for some root functions.…”
Section: Soil Biota Effects On C Stoebe Growth Depended On Soil Moist...supporting
confidence: 90%
See 1 more Smart Citation
“…Soil biota also reduced C. stoebe leaf mass area (LMA), while soil biota effects on root to shoot ratios depended on soil moisture and presence of a competitor. Similar changes in LMA have been observed previously (Hahn et al, 2018) and could be caused by AM fungi, because LMA decreases when carbon availability is lowered (Poorter et al, 2009) and AM fungal colonization induces a substantial carbon-sink (Drigo et al, 2010). Soil biota significantly reduced root to shoot ratios of C. stoebe which fits with early observations of AM fungi reducing root to shoot ratios in C. stoebe (Marler, Zabinski, Wojtowicz, et al, 1999), possibly because AM fungi substitute for some root functions.…”
Section: Soil Biota Effects On C Stoebe Growth Depended On Soil Moist...supporting
confidence: 90%
“…Further, we also chose to pool our soil inoculum from gradient end points to ensure compatible mutualists and pathogens were present. This precluded assessments of potential soil biota adaptations to soil moisture environments, which has been shown in some studies (Remke et al, 2021) but not others (Hahn et al, 2018). Finally, our study relied on shifts in relative sequence abundance, which may or may not reflect actual function.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Despite the breadth of research on plant-soil biota relationships, the role of soil microbial communities on plant phenotype is heavily limited by the scarcity of knowledge of these relationships on traits such as physiology and reproduction. Of over 70 recent studies that have examined plant phenotype in response to unmanipulated and sterilized soil microbial treatments, only four studies have examined traits related to physiology (Hahn et al, 2018;Mursinoff & Tack, 2017;Siefert et al, 2018;Xi et al, 2018) and two have examined reproductive traits (Bauer & Flory, 2011;Dudenhöffer et al, 2018). In this study we found that neither SLA nor timing of ower bud formation responded to soil microbiome origin treatments, indicating that not all plant phenotypes are in part mediated by soil microbes.…”
Section: Soil Microbial Mediation Of Plant Phenotype Varies By Plant ...contrasting
confidence: 56%
“…The largescale chemical analysis of the rhizomicrobiome, combined metagenomics, metatranscriptomics, metaproteomics and imaging mass spectrometry approaches (MSI) will help to understand the mechanisms involved in the communication between different members of the soil community (Oburger and Schmidt, 2016). Similarly, molecular databases such as Funguild and PICRUSt offer a promising framework to link taxa to function using 16S rRNA gene sequences (Langille et al, 2013;Tedersoo et al, 2014;Hahn et al, 2018). Given the spatial resolution required to investigate rhizosphere interactions (from cm to sub ”m), the unpredictability of field conditions, and the instrumental limitations (e.g., immobility) most studies seek to simulate field conditions in semi-artificial experimental conditions (Oburger and Schmidt, 2016).…”
Section: Research Methodology Of Rhizosphere Interactionmentioning
confidence: 99%